Aging reduces ABHD5 protein content in the adipose tissue of mice: The reversal effect of exercise. (14th December 2022) - Brícola, Rafael S.; Cordeiro, André V.; Crisol, Barbara M.; Braga, Renata R.; de Melo, Diego G.; Rocha, Matheus B.; Gaspar, Rafael C.; Nakandakari, Susana C. B. R.; Silva, Vagner R. R.; Anaruma, Chadi P.; Katashima, Carlos K.; Canciglieri, Raphael D. S.; et al.
Abstract: Dysfunction of the adipose tissue metabolism is considered as a significant hallmark of aging. It has been proposed that α‐β hydrolase domain containing 5 (ABHD5) plays a critical role in the control of lipolysis. However, the role of ABHD5 in the control of lipolysis during aging or exercise is unknown. Here we combined the experimental mouse model with transcriptomic analyzes by using murine and human databases to explore the role of ABHD5 in the adipose tissue during aging and in response to exercise. Transcriptomic data revealed a downregulation of Abhd5 messenger RNA levels in the subcutaneous white adipose tissue (scWAT) over time in individuals from 20 to 69 years old. Aged mice displayed dramatic reduction of ABHD5 protein content and lipolytic‐related proteins in the scWAT. Interestingly, 4 weeks of high‐intensity interval training increased ABHD5 protein level and restored the lipolytic pathway in the scWAT of aged mice. Altogether, our findings demonstrated that aging affects ABHD5 content in the adipose tissue of mice and humans. Conversely, exercise increases ABHD5 activity, recovering the lipolytic activity in aged mice. Significance statement: Dysfunction of the adipose tissue metabolism is considered as a significant hallmark of aging. Here we identify that a pivotal protein involved in the lipolysis mechanism called α‐β hydrolase domain containing 5 (ABHD5) is downregulated in adipose tissue of aged mice. Conversely, high‐intensity interval training (HIIT) recovered ABHD5 protein content and lipolysis mechanism in the subcutaneous adipose tissue of aged mice.